Development of a survey generator tool for creating questionnaires templates and collecting data / Nurul'Ain Abdullah - Abdullah, Nurul'Ain (2010)
The purpose of the study is to develop a survey generator tool. A survey generator tool is a tool for designing and creating survey from scratch that offers convenience to the surveyor as the tool are able to generate desired survey for the surveyor. Nowadays survey generator tool have limitation in services that they offered as in order to have advanced services, surveyor have to pay for them. Surveyor can only do the basic things to create survey, as they cannot customize their survey as they want. The first objective of this paper is to identify the features of a survey generator tool. Second objective is to develop the survey generator tool for creating questionnaires templates. Lastly, to test the functionality of the tool. The conclusion of this paper is, survey generator tool ease surveyor in terms of creating their survey and offers flexibility ranging from changing and rearranging the questions, in order to customize a new survey questions for the user. The challenges in completing this paper is developing the survey generator tool are not as simple as people can see or think as it is not easy to code dynamic graphical user interface in net beans such as build dynamic JButtons that can invoked action Performed when a button is clicked. And also to arrange the questions and answers as the survey really owner wants.